Effect of Tabata training program on body fat reduction in healthy inactive women - Adriana Ljubojević; Nikolina Gerdijan; Ratko Pavlović; Lejla Šebić (IP Iermakov S.S., 2023)
Background and Study Aim. Tabata training is getting more and more popular these days. Based on interval training offers metabolic booster that causes major benefits for reducing body fat storage.  It is an interval training protocol which is a cardio workout for fat loss. The aim: this study was to examine the effects of a specific 16-week Tabata intervention program on body fat reduction in inactive healthy women. Material and Methods. A non-randomized controlled trial with 2x2 statistical design was provide in this study. The research was conducted on a sample of 49 women (aged 30 to 45) employed in the administrative sector, with more than 6h of sedentary tasks in their habitual working day. It included one experimental group-EG (Tabata program, n=24) and one control group-CG (without physical activities, n=25) and two moments of evaluation: (Initial) at baseline and (Final) after 16 weeks of post intervention period. The body composition parameters and body circumference in each group was recorded. All body composition parameters were measured using a Body composition analyser (Tanita BC-418MA III). Results. The results revealed that there was statistical significance difference after Tabata training program (TTP) in EG for body composition parameters (Mean±SD) for Body mass index (kg/m²) = 22.11±2.59kg/m²; p=0.04, ES=0.07); Fat tissue (%) =25.97±4.72; p=0.03, ES=0.08) and Fat tissue (kg) =17.52±5.11; p=0.02, ES=0.10). Furthermore, there were statistical significance difference in upper-arm circumference (24.95±2.31, p=0.00, ES=0.16) and waist circumference (75.93±7.18, p=0.02, ES=0.10). The control group did not achieve significant differences in the final measurement. Conclusions. Tabata training exercise program (4 months) has been shown to be beneficial for reducing body fat in healthy inactive women